2011
DOI: 10.1007/s10096-011-1423-7
|View full text |Cite
|
Sign up to set email alerts
|

Elevated soluble urokinase receptor values in CSF, age and bacterial meningitis infection are independent and additive risk factors of fatal outcome

Abstract: The aim of the present study was to evaluate the potential role of cerebrospinal fluid soluble urokinase receptor (suPAR) level, infection and age as risk factors for fatal outcome in patients suspected of having meningitis and/or bacteraemia on admission to hospital. A total of 545 cerebrospinal fluid samples from patients with clinically suspected meningitis were sent to the Hellenic National Meningitis Reference Laboratory. Ten of 545 (1.83%) patients died. Analysis by receiver operating characteristics (RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…The AF levels of suPAR were only elevated in the presence of active infection, implying that the peritoneal infiltrate is responsible for the local level. In agreement with our results, increased local levels of suPAR in cerebrospinal fluid during bacterial meningitis and in bronchoalveolar lavage specimens from patients with inhalation trauma are associated with the extent of local inflammation. Mesothelial cells have been shown to release suPAR in response to LPS and inflammation .…”
Section: Discussionsupporting
confidence: 92%
“…The AF levels of suPAR were only elevated in the presence of active infection, implying that the peritoneal infiltrate is responsible for the local level. In agreement with our results, increased local levels of suPAR in cerebrospinal fluid during bacterial meningitis and in bronchoalveolar lavage specimens from patients with inhalation trauma are associated with the extent of local inflammation. Mesothelial cells have been shown to release suPAR in response to LPS and inflammation .…”
Section: Discussionsupporting
confidence: 92%
“…suPAR is known to increase in several inflammatory and infectious diseases, and the rise in serum level has a negative effect on the clinical course. [8][9][10] The most striking study to date regarding suPAR in patients with hematologic malignancies is that by Haastrup et al involving 20 allogeneic stem cell recipients. 11 In that study, pre-transplant suPAR values were higher than those of the control group; suPAR values were monitored weekly for 1 month post-transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, even though the CSF cultures become sterile for 24-48 h with antibiotic treatment, the high rate of mortality and neurological complications demand additional research work [5,14,23,32]. Animal research showed that bacterial lysis results in increased subarachnoid inflammation, increasing the risk of a worse outcome of the disease [3,17], as a result of releasing inflammatory interleukins through destroying bacteria [4][5][6]30].…”
Section: Discussionmentioning
confidence: 99%